(untitled) (Physical Education, Health and Social Sciences, 2025)
In the current era of uncertainty, the importance of restructuring an organization has increased even more. Among several ways of reorganizing a firm, financial restructuring stands out as one of the key strategies that organizations adopt to improve their performance. The current study aims to find the impact of corporate life cycle stages on financial restructuring. The independent variable in the study is the stages of the corporate life cycle, classified using the methodology developed by Dickinson (2011). The stages include Birth, Growth, Maturity, Shakeout, and Decline. Financial restructuring is measured through three different proxies, i.e., dividends, net debt, and net equity. Financial distress serves as a moderating variable in the study. The influence of corporate life cycle stages on financial restructuring is analyzed both individually and in the context of financial distress. The study uses a panel data set of 314 non-financial Pakistani firms across thirteen diverse sectors over ten years, from 2013 to 2022. The study utilizes a multiple regression model to investigate the impact of CLC stages on financial restructuring empirically. The results indicate that firms in Pakistan typically avoid dividend payments across all stages of the Corporate Life Cycle (CLC), except the decline stage. Financially distressed firms reduce dividend payments to shareholders throughout all stages of the corporate life cycle (CLC). firms at all stages of their lifecycle tend to increase net debt, except during the decline stage. financially distressed firms in Pakistan are inclined to adopt debt financing. When firms face financial difficulties, they typically have limited internal funds, leading them to depend more on debt. Pakistani firms utilize equity financing at all stages of their lifecycle, except during the decline stage.